Concentration, market power and performance of the Malaysian poultry industry - Umar, Mua'zu Abdulrazak (2014)
Over the last few decades, Poultry industry in Malaysia has undergone major structural changes both horizontally and vertically due to the consolidation and integration of agribusiness. As such there is increasing concern about concentration and possible exercise of market power along the industry supply chain. The general objective of this study is to examine relationship among the market structure (concentration), market power and performance of the Malaysian poultry market. The general objective is achieved through an integrated study approach segmented in two separate but related sections; the first segment is the structureconduct-performance (SCP) and market power analysis and the second segment is price transmission and market integration analysis using time-series co-integration model. The result of the SCP model suggests farm level market is moderately concentrated over the study period indicated by the CR4 61.9% and HHI 2179. Market conduct analysis shows firms’ in the industry increases their profit through market share rather than price suggesting an oligopolistic market structure. The result of the 2SLS indicates market concentration in the Malaysian poultry market has positive relationship with advertising. Industry growth has significant but negative effect on both advertisements and profit. The result revealed a two-way cause and effects existed between market concentration and industry behavior. The result of the estimated demand and supply equations of poultry market in Malaysia shows that chicken meat demand is inelastic -0.124 indicating that consumer are not sensitive to price changes. On the other hand income elasticity is elastic at 3.636 implying that poultry meat as luxury good. The cross-price elasticity with respect to beef is -2.405 rejecting beef as a substitute to chicken meat in Malaysia. Results of the market power analysis show that the coefficient of conduct parameter for the three sub-periods of 1980-1990, 1991-2004 and 2005-2010 were 0.6740, 0.5540 and 0.5790 respectively, rejecting the hypothesis that raising concentration means increasing market power. The values of the parameter lie between 0 and 1 which suggests imperfect competitive market in the Malaysian poultry industry as more farmers opt to join poultry integrators. Analysis of asymmetry price transmission model reveals that retail prices react more rapidly but not completely to increases in upstream (producer) prices than to decreases. The result of Granger-Causality suggests regional markets as independents and central market of Kuala Lumpur as dominant market. Based on the overall findings, we can postulate that vertically integrated market structure foster competition through efficiency gain as against market foreclosure as posits by the conversional SCP collusive hypothesis. The findings of the study would lead to development of new policy to increase viability, competitiveness and accessibility of the Malaysian poultry industry locally and internationally.